From Readership to Usership: Communicating Heritage Digitally Through Presence, Embodiment and Aesthetic Experience - Bertrand, Stéphanie; Vassiliadi, Martha; Zikas, Paul; Geronikolakis, Efstratios; Papagiannakis, George (Frontiers in Communication, 2021)
The primary mission of cultural institutions, including heritage sites and museums, is to perform and perpetuate Cultural Heritage (CH) by ideally transforming audiences into stewards of that heritage. In recent years, these institutions have increasingly turned to Mixed Reality (MR) tech-nologies to expand and democratize public access to CH – a trend called upon to accelerate with COVID-19 – because these technologies provide opportunities for remote connections, and moreover, can make partial remains or ruins more relatable to the public. But as emerging evalu-ations indicate, existing MR intangible and tangible Digital Cultural Heritage (DCH) applications are largely proving inadequate to engaging audiences beyond an initial fascination with the im-mersive 3D visualization of heritage sites and artefacts owing in part to misguided storytelling or non-compelling narratives. They fail to effectively communicate the significance of CH to audi-ences and impress upon them its value in a lasting way, due to their overreliance on an educa-tion-entertainment-touristic consumption paradigm. Building on the recent case made for Litera-ture-based MR Presence, this article examines how the literary tradition of travel narratives can be recruited to enhance presence and embodiment, and further incite aesthetic experiences in DCH applications by drawing on recent findings from the fields of XR, cognitive literary science and new museology. The projected effects of this innovative approach are not limited to an in-crease in audience engagement on account of a greater sense of presence and embodiment. This approach is also expected to prompt a different kind of public reception characterized by a per-sonal valuation of the heritage owing to aesthetic experience. As the paper ultimately discusses, this response is more compatible both with MR applications’ default mode of usership, and with newly emerging conceptions of a user-centered museum (e.g., the Museum 3.0), thus providing a Virtual Museum (VM) model better suited to the primary mission of transmitting and perpetu-ating CH.